Detection Trend of Meteorological Drought Using Standardized Precipitation Index (SPI) in The Dolago Watershed, Central Sulawesi - Sutapa, I Wayan; Arafat, Yassir; Rustiati, Nina Bariroh; Patricia, Ayu (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Drought events worldwide are increasingly becoming a critical issue due to their negative impacts on water resources. Therefore, it is necessary to understand the characteristics of drought to plan disaster mitigation measures. This study detected meteorological drought in the trend domain using the Standardized Rainfall Index (SPI) in the Dolago River Basin. Monthly rainfall data for 20 years (2003-2022) from two meteorological stations (Dolago Bendung and Dolago Padang) were used in this study. SPI was used to reconstruct drought events and characterize the trend of drought events. Drought frequency was estimated as the ratio of the specified severity to the total number of events. Changes in drought events were detected using the non-parametric Man-Kendall trend test. The main drought conditions detected by SPI are severe drought, moderate drought, near normal, moderate wet, very wet, and very wet conditions. From these results, the SPI value fluctuated greatly from month to month. In the first decade (2003-2012), many normal conditions occurred, and changes from wet to dry months did not occur suddenly. In contrast to the second decade (2013-2022), the normal conditions are reduced from the first decade and the weather conditions change rapidly. The SPI value, which represents seasonal conditions, shows that dry conditions in various categories are more prominent in the second decade, while wet conditions are almost the same between the first and second decades. Trend analysis shows that most SPI values ??experience a decreasing/negative trend, but not all are significant at the 90% level. The SPI value is significant in April (-1.65) and December (-3.41). It is recommended that these findings be adopted for decision-making related to the drought early warning system in the watershed